PENINGKATAN PELAYANAN ADMINISTRASI DAN INFORMASI MELALUI PEMASANGAN BANNER SOP DI DESA TANJUNG JAYA KECAMATAN PANIMBANG - Jefri, Ulfi; Madina, Listia Ulya; Setyawati, Sharla; Alamsyah, Muhammad Ghondur (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Quality public services are the government's obligation to fulfill the rights of the community, including at the village level. The preparation of Administrative Standard Operating Procedures (SOPs) is a strategic step to improve transparency, consistency, and ease of access to information. This Community Service (PkM) activity aims to encourage the Tanjung Jaya Village Government to provide services according to applicable regulations and make it easier for the community to take care of various administrative services. The innovation carried out is the manufacture and installation of SOP Administration banners at the village office as a physical information medium that can be accessed directly by residents. The implementation method includes problem identification, interviews, preparation of SOP drafts, adjustments to regulations, finalization of documents, and installation of banners. The results of the activity showed a positive response from the village government and the high enthusiasm of the community in utilizing the available information. With the SOP banner, village officials have clear work guidelines, so that public services can take place more structured, accountable, and responsive to the needs of citizens. The existence of this information media is expected to be a sustainable tool in supporting transparent and efficient village governance.